Representing linguistic communicative functions in the premotor cortex. (25th November 2022) - Chang, Wenshuo; Wang, Lihui; Yang, Ruolin; Wang, Xingchao; Gao, Zhixian; Zhou, Xiaolin
Abstract: Linguistic communication is often regarded as an action that serves a function to convey the speaker's goal to the addressee. Here, with an functional magnetic resonance imaging (fMRI) study and a lesion study, we demonstrated that communicative functions are represented in the human premotor cortex. Participants read scripts involving 2 interlocutors. Each script contained a critical sentence said by the speaker with a communicative function of either making a Promise, a Request, or a Reply to the addressee's query. With various preceding contexts, the critical sentences were supposed to induce neural activities associated with communicative functions rather than specific actions literally described by these sentences. The fMRI results showed that the premotor cortex contained more information, as revealed by multivariate analyses, on communicative functions and relevant interlocutors' attitudes than the perisylvian language regions. The lesion study results showed that, relative to healthy controls, the understanding of communicative functions was impaired in patients with lesions in the premotor cortex, whereas no reliable difference was observed between the healthy controls and patients with lesions in other brain regions. These findings convergently suggest the crucial role of the premotor cortex in representing the functions of linguistic communications, supporting that linguistic communication can be seen as an action.